Insight of Mechanism and Signaling Pathway in Pathogenesis of Diabetic Neuropathy: A Review: Pathogenesis of Diabetic Neuropathy - Ab Hamid, Norhamidar; Omar, Norsuhana; Ismail, Che Aishah Nazariah; Long, Idris (IIUM Medical Journal Malaysia, 2021)
Diabetic neuropathy (DN) is a common chronic microvascular complication of diabetes mellitus. The features of DN include allodynia, hyperalgesia, abnormal or loss of sensation of nerve fibers. The clinical features will contribute to poor quality of life, disrupt sleep, lead to depression, and increases mortality. Current drug treatments have been shown to alleviate the symptoms of DN but failed to treat the underlying causes of DN. Therefore, a better understanding of the molecular mechanisms underlying the development and progression of DN is needed for early diagnosis and intervention and understanding the failure of existing treatments. Identification of potential mechanisms is critical for better prediction of progression and for designing preventive therapies. DN's exact pathogenesis is incomplete, although it is understood that its multifunctional dysfunction involving many signaling pathways. This review summarized the common deterioration of signaling pathways and mechanisms involved in DN pathogenesis.